Traditional uses of medicinal plants in Solhan (Bingol-Turkey) - Polat, Ridvan; Cakilcioglu, Ugur; Satil, Fatih (Elsevier Ireland Ltd, 2013)
Ethnopharmacological relevance: This study has identified not only the wild plants collected for medical purposes by local people of Solhan District in the Eastern Anatolia Region, but also the uses and local names of these plants. It tried to provide a source for researchers studying in ethnobotany, pharmacology and chemistry by comparing the information obtained from traditionally used herbs with previous laboratory studies. Aim of the study: This study aims to identify wild plants collected for medical purposes by the local people of Solhan District located in the Eastern Anatolia Region of Turkey and to determine the uses and local names of these plants. Materials and methods: A field study had been carried out for a period of approximately 2 years (2011-2012). During this period, 214 vascular plant specimens were collected. Demographic characteristics of participants, names of the local plants, their utilized parts and preparation methods were investigated and recorded. The plant species were collected within the scope of the study; herbarium materials were prepared; and the specimens were entitled. In addition, the relative importance value of the species was determined and informant consensus factor (FTC) was calculated for the medicinal plants included in the study. Our research area also includes people with Kurdish and Zaza ethnic origins. Results: 82 plants were found to be used for medical purposes before in the literature analysis of the plants used in our study, while 9 plants were found to have no literature records. The most common families are Asteraceae (12 plants), Rosaceae (10 plants), and Lamiaceae (9 plants). The medicinal uses of Anthriscus cerefolium (L) Hoffm., Arum elongnatum Steven, Astragalus lamarckii Boiss., Chaerophyllum bulbosum L, Crataegus atrosanguinea Pojark., Hordeum bulbosum L, Pastinaca armena Fisch. & Mey., Prunus kurdica Fenzl ex Fritsch, Sium sisarum L var. lancifolium (M. Bleb.) Thell. that we found were used in our study area and recorded for the first time. No information could be obtained regarding the names of two wild plants that are being used in Solhan. In Turkey, local plant names display differences especially due to local dialects. The plants used in Solhan are known by the same or different local names in various parts of Anatolia. Conclusion: In the research area, local people were found to use 82 plants from 31 families for curative purposes. The respondents of the questionnaire are Turkish citizens, with various ethnic backgrounds. Mean age of the respondents was 55 years. These plants are used in the treatment of many diseases. Comparison of the data obtained in this study with the experimental data obtained in the previous laboratory studies derived from the plants growing in Solhan proved ethnobotanical usages to a great extent. Literature review indicated that the curative plants that grow in Solhan are used in different parts of the world for the treatment of similar diseases. These plants, used for the treatment of various diseases, are abundantly found in this region. Drying of the medicinal plants enabled the local people to use them in every season of the year. Published by Elsevier Ireland Ltd.
Keywords: Ethnobotany; Medicinal plants; Use value; Informant consensus factor; Solhan; Bingol